Effect of host plants on the development, survivorship and reproduction of Grapholita molesta (Lepidoptera: Tortricidae) under laboratory conditions. Issue 4 (22nd April 2016) - Yang, Xiao‐fan; Fan, F.; Ma, Chun‐seng; Wang, Chong; Wei, Guo‐shu
Abstract: To seek sufficient resources for growth, survival and reproduction, most insect species must tackle host selection problems. The development, survivorship and fecundity of the oriental fruit moth Grapholita molesta (Busck) on apricot Prunus armeniaca L., plum Prunus salicina L., nectarine Prunus persica var. nectarina L. Batsch, peach Prunus persica L., pear Pyrus sorotina Will. and apple Malus domestica Mill. were determined to test host suitability in the laboratory. Larval development rate was faster, and survival rate was higher on plum and nectarine compared with the other fruits. Adult longevity and the duration of oviposition were significantly longer on nectarine. Adult fecundity varied significantly among the tested host plants, with the highest fecundity being observed on apple (135.63 eggs/female), followed by pear (104.90 eggs/female). The intrinsic rate of increase ( rm ) was greater on pear and apple (0.1574 and 0.1221 eggs per female per day, respectively). Different abilities to develop and reproduce on various host plants partly explain the seasonal host selection of G .  molesta .